Hubungan Pengetahuan Dengan Kesiapsiagaan Perawat Menghadapiancaman Bencana Gempa Bumi Di Rumah Sakit Wirabuana Palu - Wendi Muhammad Fadhli (Pusat Riset dan Inovasi Nasional, 2021)
Disaster preparedness is often overlooked by nurses who do not have the knowledge, skills and experience in dealing with disasters. Preparedness is an effort that is carried out to anticipate the occurrence of disasters in order to reduce the impact caused by disasters. The purpose of this study was to analyze the relationship between knowledge and nurse preparedness in facing the threat of earthquake disaster at Wirabuana Hospital Palu. This type of research is quantitative research with a cross sectional approach. The population in this study were all nurses at Wirabuana Hospital Palu, totaling 78 people. The sample is the total population. The sampling technique in this study was total sampling by taking all members of the population into the sample. The results of the study were analyzed using univariate and bivariate analysis. The results showed that most nurses who had good knowledge about earthquakes were 76.9%, most nurses were ready to face the threat of earthquake disaster, 69.2%. The results of the chi square statistical test obtained a value of p = 0.000 (p value <0.05), this means that statistically there is a relationship between knowledge and nurse preparedness in facing the threat of earthquake disaster at Wirabuana Hospital Palu. Conclusion: there is a relationship between knowledge and nurses' preparedness in facing the threat of earthquake disaster. Suggestions for Wirabuana Hospital Palu to improve nurses' preparedness in facing the threat of earthquake disaster through training or simulations about disasters so that nurses are better prepared to face the threat of earthquake disaster.